The Judge’s Oversight Function on Unreasonableness in Disciplinary Actions : A Comparative Study - Smairan, Abdalelah (Journal of Legal Sciences, 2023)
The Administrative agency enjoys certain privileges when issuing disciplinary actions on a public servant. As the only entity conferred with the authority to issue disciplinary action to actualize certain aims, like establishment of, or amendment or repealing of certain legal provisions. Public service is regarded as the most widespread sector due to the employer-employee working relationship between the administrative agency and the public servant. The aim of disciplinary action is to serve deterrent to the employee from committing similar offence in the future and guaranteeing of smooth running of the organization and effective delivery of work. Therefore, the administrative agency must commit to achieving this aim, without being outrageous in taking disciplinary action, rather the punishment should be proportionate to the offence committed. It is from this perspective the oversight function of the Administrative law Judge becomes important in ensuring that the punishment imposed is not unreasonable.